Influence of self-perceived multicultural counselling competence on self-efficacy among counselling teachers - Harun, Maizatul Mardiana (2015)
The purpose of this study was to investigate the influence of self-perceived multicultural counselling competence on self-efficacy among counselling teachers. This study was also designed to explore the relationship between multicultural counselling competency and self-efficacy among counselling teachers. Additionally, this study aimed to identify the relationship between selected counselling teachers’ demographic variables such as age, years of working experience and multicultural training received with counselling teachers’ self-perceived multicultural counselling competence and self-efficacy. This quantitative-correlational research was carried out among secondary school counselling teachers in Negeri Sembilan. A simple random sampling method was used to get 200 respondents. Each respondent received a set of questionnaire via post, and a total of 167 counselling teachers participated in the study. The questionnaire consists of three parts; (i) demographic questionnaires, (ii) Multicultural Counselling and Training Survey-Revised (MCCTS-R), and (iii) Multicultural Counselling Self-Efficacy-Racial Diverse (MCSE-RD) form. The MCCTS-R and MCSERD were adapted and translated into the Malay language. As the focus of the study, the linear regression analysis was conducted to determine the influence of self-perceived multicultural counselling competence on counselling teachers’ self-efficacy. The relationship between self-perceived multicultural counselling competence and selfefficacy was tested by conducting the Pearson product moment correlation coefficient analysis. Similar analysis was conducted to examine the relationship between age, number of multicultural trainings received and years of working as a counselling teacher with multicultural counselling competencies and self-efficacy. A series of descriptive analyses were conducted to assess the level of the counselling teachers’ self-perceived multicultural counselling competence and self-efficacy. The descriptive analysis revealed that the respondents scored at the moderate level for self-perceived multicultural counselling competence and self-efficacy. The main finding of the study is that the self-perceived multicultural counselling competence was found to be a significant predictor of counselling teachers’ self-efficacy. Specifically, the selfperceived multicultural counselling competence contributed 28.2% of influence on the variability of counselling teachers’ self-efficacy. The Pearson product moment correlation coefficient showed that there is a significant, positive and strong correlation between self-perceived multicultural counselling competence and self-efficacy. The results of the study showed that age was related to the counselling teachers’multicultural counselling competence only, while the number of multicultural training experiences were related to both the counselling teachers’ multicultural counselling competence and their self-efficacy. In conclusion, the finding of this study suggests that counselling teachers who perceived themselves as somehow multiculturally competent, also believe themselves as efficacious in handling multicultural counselling sessions. Thus is very important that this aspect is given due attention by the training institutions in their counselling teacher preparation programs,and also by the Ministry of Education in the counselling teacher professional development. Future studies should control the sample based on demographic variables such as gender, ethnicity and geographical school setting to provide different insight related to the development of self-efficacy.